Sleep and Circadian Rhythmicity in Adult ADHD and the Effect of Stimulants: A Review of the Current Literature. (January 2017) - Snitselaar, Mark A.; Smits, Marcel G.; van der Heijden, Kristiaan B.; Spijker, Jan
Objective: This review updates information on sleep and circadian rhythmicity in adult ADHD, especially circadian rhythmicity and the influence of stimulants.Method: Investigations into sleep, chronotype, and circadian rhythm in adult ADHD were searched in the Cochrane Library, Embase, Medline, and PsycInfo databases.Results: ADHD in adults is associated with longer objective sleep latency, irrespective of insomnia complaints. Sleep maintenance is disturbed and waking up time is delayed. Adult ADHD is associated with increased eveningness, delayed dim light melatonin onset (DLMO), and later waking up time. Stimulant treatment induces delay of nonparametric circadian parameters, whereas light therapy (LT) induces shifts toward morningness, which is associated with a reduction of ADHD symptoms.Conclusion: Adult ADHD is associated with delayed circadian rhythmicity and analogous sleep characteristics, which are typical of a delayed sleep phase disorder. Stimulants induce delay of circadian rhythmicity.